Exploring the perspectives and identifying the challenges of postnatal mothers delivered at a not-for-profit tertiary care referral centre in Vellore, South India: a qualitative study - Mapitha; Abraham, Nitin Alexander; Shabeer, Muhammed; Jacintha, Angeline; Mano, Grace; Priscilla, Ruby Angeline; Parveen, Sajitha; Kumar, Manish; Bakshi, Ravleen; Mathews, Jiji Elizabeth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Our study aimed to explore the perspectives of postnatal women and identify the emotional, psychological and physical challenges in the post-natal period. Methods: Women who delivered in a not-for-profit tertiary referral centre in South India and had postnatal visits in the last quarter of 2022 were contacted for an in-depth interview after verbal informed consent. Snowball sampling was used to contact postnatal women who fulfilled the eligibility criteria till data saturation was reached. Result: Overall, 27 interviews were recorded based on the inclusion criteria of the study. After the initial coding, five themes evolved namely: Emotional challenges and response to motherhood; physical pain and self-care; cultural practices and support; financial responsibilities and support; and postnatal care beyond maternal nutrition and breastfeeding. Women who accepted their new role as mothers found ways to manage their time between self-care and care of the newborn. Choosing to stay at home for child care was difficult for women who were working earlier. Mothers were apprehensive of the next pregnancy and sexual health was affected in women who decided not to get pregnant again. Conclusion: Pain interfered with self-care, care of the newborn and daily routine. Nutrition of postnatal women and perineal and newborn care were influenced by local beliefs that interfered with the discharge advice given by health care professionals. Postnatal women decided to go to a closer health centre for minor illnesses of the newborn or postpartum complaints. Birth spacing, Contraception, urinary and bowel symptoms were not addressed regularly at the time of discharge.